Auxiliary Converter with Voltage Closed-loop Control - TANG Zihui; JIANG Xuejun; WEI Gang (Kongzhi Yu Xinxi Jishu)
According to the operation characteristics of auxiliary converter, based on voltage closed-loop and constant control strategy of the ratio between voltage and frequency square, it studied output voltage fluctuation of auxiliary converter and heavy load impact from the current in the process of speed modulation by applying the Matlab simulation analysis model. The test results show that power supply quality of the auxiliary converter can basically meet the requirements of the auxiliary load.